Transmural Heterogeneity and Remodeling of Ventricular Excitation-Contraction Coupling in Human Heart Failure - Lou, Qing (2011)
BACKGROUND: Excitation-contraction (EC) coupling is altered in the end-stage heart failure (HF). However, spatial heterogeneity of this remodeling has not been established at the tissue level in failing human heart. The objective is to study functional remodeling of EC coupling and calcium handling in failing and nonfailing human hearts. METHODS AND RESULTS: We simultaneously optically mapped action potentials (AP) and calcium transients (CaT) in coronary-perfused left ventricular wedge preparations from nonfailing (n = 6) and failing (n = 5) human hearts. Our major findings are: (1) CaT duration minus AP duration was longer at sub-endocardium in failing compared to nonfailing hearts during bradycardia (40 beats/min). (2) The transmural gradient of CaT duration was significantly smaller in failing hearts compared with nonfailing hearts at fast pacing rates (100 beats/min). (3) CaT in failing hearts had a flattened plateau at the midmyocardium; and exhibited a “two-component” slow rise at sub-endocardium in three failing hearts. (4) CaT relaxation was slower at sub-endocardium than that at sub-epicardium in both groups. Protein expression of sarcoplasmic reticulum Ca(2+)-ATPase 2a (SERCA2a) was lower at sub-endocardium than that at sub-epicardium in both nonfailing and failing hearts. SERCA2a protein expression at sub-endocardium was lower in hearts with ischemic cardiomyopathy compared with nonischemic cardiomyopathy. CONCLUSIONS: For the first time, we present direct experimental evidence of transmural heterogeneity of EC coupling and calcium handling in human hearts. End-stage HF is associated with the heterogeneous remodeling of EC coupling and calcium handling.